Behavioural and environmental risk factors for household injuries: semistructured interviews with health professionals and mothers in Iran. Issue 1 (25th January 2023) - Lael-Monfared, Elaheh; Rakhshanderou, Sakineh; Ramezankhani, Ali; Ghaffari, Mohtasham
Abstract : Background: Injuries are increasing global public health problems, causing disability and death among children. This has considerable financial, emotional and social eﬀects on families and society. This study aimed to investigate the behavioural and environmental factors leading to unintentional home injuries and attempts to highlight the pivotal role of mothers' behaviour and performance to provide a safe place for children at home. Methods: The current research is a qualitative study of a directed content analysis type. The data were gathered through semistructured interviews conducted in participants' workplaces, namely universities, research centres and health centres. In some cases, telephone interviews were conducted within 3 months, from February 2021 to May 2021 in Tehran, Iran. The participants were selected through non-probability and purposive sampling. All the recorded interviews and notes were accurately evaluated, and data analysis was performed based on the content analysis. There were 29 interviews in total: 12 interviews with mothers, 9 with treatment and prevention specialists, and 8 with researchers. Results: A total of 66 factors, 6 subcategories and 2 main categories were extracted after analysing the interviews. The main categories included environmental and behavioural factors. The subcategories included house infrastructure, house equipment/furniture, children's equipment/furniture, provision of precarious conditions, access to hazardous substances and appliances, and unsafe arrangement of furniture. Conclusion: Despite the existing obstacles such as the long-term implementation, financial difficulties and overcomplicated policy-making process, health interventions can make it possible for mothers of children under the age of seven to adopt preventive measures through appropriately designed instructions and optimal use of existing facilities.